2020
DOI: 10.1177/016146812012201206
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating to Success: The Impact of Florida's Developmental Education Reform on Credit Accumulation

Abstract: Background/Context Underprepared students at community colleges are often assigned to a sequence of developmental education courses that can substantially delay, or even halt, their progress to degree completion. In 2014, Florida implemented a comprehensive reform under Senate Bill (SB) 1720 that allowed the majority of incoming students to enroll directly into college-level courses, while remaining developmental education courses were offered in new instructional modalities that were designed to be completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Moreover, the reform also has some unexpected consequences. For example, although SB 1720 of 2013 has no mandate on changes in college-level courses, many institutional leaders reported that they made adjustments to the college-level courses, with more students of different levels of academic preparation now enrolling in them (Mokher et al, 2020). SB 1720 of 2013 also led to increased campus-wide coordination and the culture of fostering student access (Brower et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the reform also has some unexpected consequences. For example, although SB 1720 of 2013 has no mandate on changes in college-level courses, many institutional leaders reported that they made adjustments to the college-level courses, with more students of different levels of academic preparation now enrolling in them (Mokher et al, 2020). SB 1720 of 2013 also led to increased campus-wide coordination and the culture of fostering student access (Brower et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many more students enrolled and completed introductory college-level English and math courses within the first year of enrollment after the reform (Park-Gaghan et al, 2020). Students also attempted and earned more college credits following the DE reform (Mokher et al, 2020). Existing studies also suggest that students of color benefited more from the DE reform than did White students, closing the racial gap in student outcomes (Mokher et al, 2020; Park-Gaghan et al, 2020).…”
Section: Study Context and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, following the reform, intermediate algebra and gateway math courses enrollment rates increased by 8.19 and 4.89 percentage points, respectively; cohort-based passing rates increased by 3.48 and 2.94 percentage points in intermediate algebra and gateway math courses (Park-Gaghan et al, 2020). Moreover, students have accumulated an additional 0.3 college credits by the third year after the reform (Mokher et al, 2020). Moreover, studies indicated that Black and Hispanic students tend to experience even greater gains from the reform than White students, reducing existing achievement gaps (Mokher et al, 2020; Park-Gaghan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies suggest that the developmental education reform in Florida has contributed to an overall increase in student success in terms of introductory college-level course completion and college-level credit accumulation within the first year of enrollment among all FTIC students (Mokher, Park-Gaghan et al, 2020; Park-Gaghan et al, 2020). These positive outcomes are the result of a combination of the different components of the reform.…”
Section: Policy Context and Literature Reviewmentioning
confidence: 99%